Scientific substantiation of standards of health physical activity for primary-school-age children (Environment & Health, 2022)
The aim of the study was to determine the optimal volume of primary-school-age children's physical activity to improve their adaptive capabilities.Materials and methods. The features of physical activity, social factors, anthropometric, and physiological parameters of 297 students in grades 1-4 of schools in Sumy were studied using diaries that parents filled out during the week and examination by a paediatrician (2016). The duration of moderate-to-vigorous physical activity (MVPA) was determined. The adaptive-reserve capabilities (ARV) integral indicator was calculated. ARV due to the characteristics of physical development, and the functioning of the autonomic nervous and cardiovascular systems of the child. Descriptive statistics, contingency tables, dispersion, correlation analysis, and linear regression models were used.Results. We have established that the proportion of children with an unsatisfactory level of adaptive-reserve capabilities among primary-school-age children was about 40%. A trend towards a decrease in ARV in children with chronic diseases was revealed. A relationship between ARV and the duration of sports activities was established (p0.2). The weekly duration of MVPA in children who play organized sports is higher than in those who do it on their own (p
Keywords: children of primary school age; health-improving physical activity; adaptive-reserve capabilities; health; moderate-to-vigorous physical activity